Efficacy and Safety of Topical 5% Azelaic Acid Solution Versus 2% Minoxidil Solution in the Treatment of Female Pattern Hair Loss - Thanomkitti, Kanchalit; Pruksaeakanan, Chutipon; Subchookul, Chanika; Charoenpipatsin, Norramon; Triwongwaranat, Daranporn; Varothai, Supenya; Thuangtong, Rattapon; Chumnumrat, Tanyalak (Siriraj Medical Journal, 2023)
Objective: To determine the efficacy and safety of 5% azelaic acid solution in comparison with 2% minoxidil solution in the treatment of FPHL. Materials and Methods: Twenty-six FPHL patients with Ludwig grade I or II were randomly treated with 5% azelaic acid solution or 2% minoxidil solution twice daily for 6 months. At baseline, 2, 4, and 6 months, hair density and hair shaft diameter were assessed at the targeted fixed area. At 6 months, patient and investigator assessments of hair growth were performed using a 7-point scale. Results: Hair density and hair shaft diameter in the patients treated with 5% azelaic acid and 2% minoxidil solution were significantly increased compared to the baseline in all cases and visits (P < 0.05). There were no statistically significant differences in hair density and hair shaft diameter changes between both groups (P > 0.05). Both the investigator and patient assessments were comparable between both groups at 6 months. Pruritus was the major adverse effect reported in both groups, but only mild and all could be tolerated. Conclusion: 5% Azelaic acid solution might be an effective treatment for FPHL, comparable with 2% minoxidil, and could be an alternative treatment for FPHL in minoxidil-allergic patients and pregnant women.